SEKILAS SEJARAH KEDATANGAN DAN BUDAYA KERAMIK ORANG CINA DI SINGKAWANG - Ida Bagus Putu Prajna Yogi (Naditira Widya, 2008)
Ceramic-making technology.Singkawang is a city in the Province of West Kalimantan, which inhabited mostly by the Chinese. The natural potency of Kalimantan’s western region and its strategic location on the Chinese trade route was probably one of aspects, which lead the Chinese to travel and inhabit in that specific area then. Up until now, the number of Chinese in West Kalimantan, especially in Singkawang, have been increasing and even outnumbered indigenous people of Kalimantan. Such increase in population has simultaneously encouraged the Chinese ancestral culture to flourish in Singkawang, which for instance reflected by the similary of city-form between Singkawang and those of China mainland’s. Ethnoarchaeologically, the ‘Tungku Naga’ or Dragon Klin stands out as the most striking phenomenon of the old Chinese tradition with its traditional ceramic production in Singkawang, which may well be rare attribute and yet scarcely found in China nowadays. This article discuss the arrival of Chinese in the Indonesian Archipelago and their